A study of a flowslide with significant entrainment in loess areas in China. Issue 14 (14th July 2017) - Zhang, Fanyu; Kang, Chao; Chan, Dave; Zhang, Xiaochao; Pei, Xiangjun; Peng, Jianbing
Abstract: Flowslides are a frequent type of natural disaster in loess areas and may result in the significant loss of properties and/or casualties. The Dagou flowslide is a typical event in a loess area and is accompanied by significant sediment entrainment. To analyze the mechanisms responsible for flowslides and to obtain the parameters for a runout analysis, a field investigation was conducted. Specimens were sampled on site to carry out laboratory tests, including a triaxial test, sieve analysis, and chemical component analysis. The parameters were used in the runout study employing an energy‐based runout model. An analytical entrainment model was adopted to calculate the entrainment after considering physical properties and the mechanism of the entrainment process of the loess. Finally, the entrainment model was incorporated into the runout model to simulate the post‐failure process of this case. Energy dissipation due to the deformation of slices was considered as it was thought to be important for a slide with a significant deformation. The simulation results were compared with the measurements, including runout distance, total volume, erosion depth, deposition height at different sections, and velocities at specific locations. The results indicate that the energy‐based runout model, together with the entrainment model, can capture the kinematic characteristics of the Dagou flowslide. Therefore, it is feasible to use this model to predict the runout characteristics of flowslides in similar areas. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : This paper studied a typical flowslide in a loess area which was accompanied by significant sediment entrainment. Field investigation together with laboratory tests were carried out to obtain parameters which were used following runout study. The simulation results were compared with the measurements and field observation showing the energy‐based runout model, together with the entrainment model, can capture the kinematic characteristics of the Dagou flowslide.